Shear Strength of the Mixed Adhesive Joint Silyl Modified Polymer-Epoxy in Single Lap Joint Aluminum Triyono / Sri Hastuti and Neng Sri Suharty - Triyono, Sri Hastuti; Neng, Sri Suharty (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Shear strength of mixed adhesive joints (MAJ) silyl modified polymer (SMP)–epoxy (EP) in a single lap joint (SLJ) aluminum to aluminum has been investigated. Single lap joint specimens were made according to ASTM D-1002 standard. Three levels of mixed adhesive thickness of 0.2; 0.4; and 0.6 mm were used while the variations of mixed adhesive composition were 100%EP, 75%SMP:25%EP, 50%SMP:50%EP, 25%SMP:75%EP, 100%SMP. Sandpapering grid of 150 and acetone cleaning was performed on Aluminum surface. The pressure of 0.1 Mpa and post-curing of 100oC for 100 minutes were subjected on the mixed adhesive joint specimens. Shear tests and failure surface investigations were conducted to analyze the strength of the mixed adhesive joints. The addition of silyl modified polymer to epoxy decreases the shear strength and the shear modulus but increases the elongation of the mixed adhesive joints. The mixed-adhesive joint of 25%SMP:75%EP has the highest shear strength, even it is higher than that of the adhesive joint of 100%EP. There is no significant effect of ad